MEMBANGUN KEPATUHAN WAJIB PAJAK UMKM MELALUI PERAN KEADILAN PAJAK DAN KEPERCAYAAN WAJIB PAJAK - Astuti, Puji; Faisol, Faisol; Suhardi, Suhardi (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
The goal of this study is to clarify how procedural fairness, distributive justice, and taxpayer trust all contribute to increased taxpayer compliance with MSMEs in Nganjuk Regency, Indonesia. The study does this using a positivist paradigm approach and a judgment sampling technique. A Google Forms-created questionnaire that was partly distributed in-person and online was used to collect the data. In addition, 120 respondents' responses were collected. According to the study's findings, the Nganjuk Regency's MSME taxpayers' voluntary compliance is highly influenced by procedural fairness, distributive justice, and taxpayer trust. Key Words: fairness, tax, taxpayer compliance, MSME